-4(-5+3y)+7y+5=0

Simple and best practice solution for -4(-5+3y)+7y+5=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(-5+3y)+7y+5=0 equation:



-4(-5+3y)+7y+5=0
We add all the numbers together, and all the variables
-4(3y-5)+7y+5=0
We add all the numbers together, and all the variables
7y-4(3y-5)+5=0
We multiply parentheses
7y-12y+20+5=0
We add all the numbers together, and all the variables
-5y+25=0
We move all terms containing y to the left, all other terms to the right
-5y=-25
y=-25/-5
y=+5

See similar equations:

| 7y-14+10=3y-12-2 | | 13+b/12=24 | | 4(x+2)+6=-18 | | (3x-10)+(110-x)=90 | | 2x+2(x-4)=40 | | 52+x=520 | | 4^x+4=5^2x*5 | | 8x^2+74x+18=0 | | 0.75x=0.666666 | | 3/5r-10=20 | | 13x+15=11x=25 | | (110-x)+(2x)=90 | | 3/5r=30 | | 2x2+12x=-3 | | 2x=350-50 | | 2.4–0.2x=1.4 | | 6x+3=6+18 | | X-(15x-5)=-(-3x+5) | | X+2x=350-50 | | 5+1.25m=25 | | 9(2-3r)-29=8r-(r-23) | | 3q-40=-7q | | 0.9r+0.5=8.6 | | 3f=3f+48 | | 0.42=0.06y | | P-1=(5p+3p)-8 | | 8(x-9)=96 | | 16f-24=16+56f | | 5x-3=3/8x-3 | | 13.27=37.72-n | | 3-b2=13 | | 4x+13=5x+15 |

Equations solver categories